Septocystis (Polyporales, Basidiomycota), a new genus of Polyporaceae from Southern China - Huang, Fu-Chang; Lin, Jian-Tian (Phytotaxa, 2025)
A new genus Septocystis gen. nov. was set up during the macrofungal diversity survey in southern China. Phylogenetic analyses of ITS+nLSU+RPB2 dataset showed that the new genus belongs to the family Polyporaceae. Furthermore, it is sister to Pseudomegasporoporia in the core polyporoid clade of Polyporales with a monophyletic lineage. Distinguishing characters of the new genus are its basidiomata resupinate; hyphal system dimitic; generative hyphae bearing clamp connections, skeletal hyphae frequently branched, usually well differentiated from the main part in trama; dendrohyphidia absent, hyphal pegs present; cystidia fusoid, long clavate to flask shaped, usually with 1–3 septa at tip; cystidioles fusoid, long clavate to flask shape; basidia barrel-shaped to cylindrical; basidiospores cylindrical, IKI−, CB+. A new species Septocystis minor is described. Taxonomic descriptions and illustrations are presented.